A MODEL FOR POROSITY EVOLUTION DURING CREEP COMPACTION OF SANDSTONES - He W.; Hajash A.; Sparks D. (My University, 2002)
A coupled creep-compaction and chemical-reaction model is developed to predict the porosity evolution for quartzose sandstones as a function of strain. The model also demonstrates the relative importance of grain-contact dissolution and cementation for both uniaxial and isotropic compaction. Theoretical analysis indicates that porosity reduction during compaction of sandstones is nonlinearly related to strain. In open systems, porosity loss is also related to grain packing, stress state, and pore-fluid saturation state. Grain-contact dissolution is the dominant mechanism for porosity loss in a closed system and, with increasing compaction, cementation becomes increasingly important. Compared to uniaxial compaction, isotropic compaction leads to more porosity loss due to grain-contact dissolution, but less porosity loss due to cementation. With compaction, pore-fluid saturation state has an increasing effect on porosity loss. Higher saturation state enhances porosity loss due to cementation.
Keywords: POROSITY; COMPACTION; PRESSURE SOLUTION; CEMENTATION; SATURATION